2021
DOI: 10.5603/pjnns.a2020.0080
|View full text |Cite
|
Sign up to set email alerts
|

Polish validation of the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS battery): correlation of cognitive impairment with mood disorders and fatigue

Abstract: Background: Cognitive impairment is recognised as a significant clinical issue in Multiple Sclerosis (MS). It can occur at any stage of the disease, affecting quality of life, occupational activity, and adherence to therapy. This makes the availability of a validated assessment tool for detecting and monitoring cognitive dysfunction in multiple sclerosis essential. The Brief International Cognitive Assessment for Multiple Sclerosis is a practical and simple means of administering a battery of three neuropsycho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…The specific significance of this study is attributed to the contribution of the LDST validation for the population suffering from MS in the Croatian-speaking area and the ability of creating preconditions for the BICAMS validation [ 9 , 22 , 23 ]. The validation of BICAMS in pwMS has been performed in different countries [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and inquires that authors tend to apply specific similar tests in their country if the existing proposed tests through the BICAMS battery (comprising of SDMT, California Verbal Learning Test-II, and the Brief Visuospatial Memory Test-Revised) were not available or could not be applied in their country for certain reasons [ 25 , 34 , 36 ]. Future studies might compare the LDST and SDMT in pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…The specific significance of this study is attributed to the contribution of the LDST validation for the population suffering from MS in the Croatian-speaking area and the ability of creating preconditions for the BICAMS validation [ 9 , 22 , 23 ]. The validation of BICAMS in pwMS has been performed in different countries [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ], and inquires that authors tend to apply specific similar tests in their country if the existing proposed tests through the BICAMS battery (comprising of SDMT, California Verbal Learning Test-II, and the Brief Visuospatial Memory Test-Revised) were not available or could not be applied in their country for certain reasons [ 25 , 34 , 36 ]. Future studies might compare the LDST and SDMT in pwMS.…”
Section: Discussionmentioning
confidence: 99%
“…The study omitted the exploration of sleep quality, possible other sleep disorders, and the presence of symptoms of affective disorders among participants, which is important in terms of sleep paralysis. We also did not assess cognitive functions that may be important in the development of sleep disorders, including sleep paralysis [67][68][69]. In the current study, we focused on a limited number of variables that could affect SP.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the current study investigated the relationship between executive functions and intensity of depression symptoms as well as duration of the disease. Many studies point out that depression affects cognitive function, including executive functions [ 38 , 39 ]; however, other studies suggest there is no correlation between depression indicators and cognitive measures [ 3 , 40 ]. Notably, however, conclusions about the effect of depression on cognitive functions, such as attention and executive functions, cognitive flexibility, verbal fluency, set-shifting, suppression, working memory and planning are frequently drawn based on comparative assessments of patients with diagnosed unipolar depression and with no symptoms, rather than with isolated symptoms [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition to neurological symptoms, many patients present difficulties in cognitive functioning, which further affects the quality of their lives [ 3 ]. The percentage of patients with signs of cognitive impairment reported in different studies is varied, ranging between 25% and 70%, depending on the specific characteristics of the condition, as well as approach to recruitment (hospitals, rehabilitation centres versus population studies) and adopted definition of cognitive impairments [ 1 , 3 , 4 ]. It has been suggested that the progressive variant of MS leads to more severe cognitive impairments than RRMS [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation